Peran Kelompok Tani dalam Ketahanan Pangan Rumah Tangga: Studi Kasus Lumbung Pangan Desa Kamubheka Kecamatan Maukaro Kabupaten Ende - Kristiani Nindi; Marthen R. Pellokila; Fransina W. Ballo (Universitas Veteran Bangun Nusantara, 2024)
This research aims to determine the influence of the role of farmer groups and strategies for overcoming debt arrears on household food security in Kamubheka village. The population in this research was 80 people and the sample obtained using the Sloving formula calculation was 44 village employees and members of farmer groups. In this research using quantitative research methods. The data collection technique in this research uses a questionnaire with a Likert measurement scale. The data analysis technique uses multiple linear regression analysis techniques with calculations using the SPSS program. The results of this research show that the role of farmer groups has a significant influence on household food security in Kamubheka Village. Based on the results of the analysis, it appears that the role of farmer groups makes a major contribution to increasing household food security. In conclusion, the role of farmer groups in food security is very crucial and can meet the food needs of households in Kamubheka village. And the strategy for dealing with debt arrears implemented by farmer groups has a significant influence on household food security in Kamubheka Village. Based on the analysis results, improvements in this strategy can significantly increase household food security. By overcoming debt arrears, farmer groups can ensure that food storage remains stable and is able to provide sufficient food for the entire village community.